Early Islamic Cosmopolitanism? Constructing the ʾUmma of India in Pre-Mongol Muslim Scholarship. (20th June 2019) - Hayes, Edmund
Abstract : This article analyzes possible avenues for the study of a pre-Mongol Islamic cosmopolitanism. The ways in which the archetypically idolatrous land of India is treated by Islamicate thinkers of the ʿAbbasid empire and after illuminates an Islamic cosmopolitanism that managed to incorporate the other into its view of human history and religious history. Two major fields for the generation of cosmopolitan ideas are analyzed: narratives drawn from historiography, and taxonomies erected by theological-heresiographical works. Both frameworks rely on a Muslim model of history and society in which divine truth and guidance are mediated to the communities (ʾumma, ʾumam) of the world firstly by a prophet, but also by sages and philosopher-kings: figures who play important roles in Muslim accounts of India. Through applying these "universal" categories to Indian subject-matter, Muslim thinkers were able to depict Indians as partners in the human struggle to attain and preserve truth, albeit falling short of the Muslim community in various ways. In both the historiographical and the heresiographical fields, cosmopolitan and anti-cosmopolitan trends are observable. By incorporating Indian narratives into a universalizing historical vision, Masʿūdī can best be seen to approach a cosmopolitan sensibility among thinkers within historiographic discourse. Bīrūnī goes furthest among the thinkers working within a theological-heresiographical framework in analogizing Indian philosophy with Muslim thought. It is argued that both thinkers achieve a kind of cosmopolitanism only through an elitist denigration of the commoners of their communities. In addition, their cosmopolitanism was predicated on imperial expansionism into India. Attribution-NonCommercial-NoDerivatives: CC BY-NC-ND